Effects of Leadership Styles on Employee Retention in the Public Sector of Jamaica - Davis, Carlene (Digital Repository of Theses, 2024)
This research paper aims to fill the gap in the existing literature regarding the effects of leadership styles on employee retention in the public sector of Jamaica and the Caribbean region as we operate similarly. By conducting a comprehensive study within this specific context, the research seeks to provide insights and recommendations tailored to the unique challenges and dynamics of the public sector in Jamaica. The study employed a mixed research method involving six public sector agencies encompassing various sectors, including security, health, education, housing, justice, and technology. A response rate of 52 per cent was achieved from the survey ensuring a robust data set for analysis. The findings of this study indicate that leadership style has a significant impact on employee retention in the public sector of Jamaica. Additionally, the study reveals that the work environment and compensation play a crucial role in intensifying the effects of leadership style on employee retention. The research suggests that the public sector's current employee retention efforts are falling below expectations, highlighting the need for targeted interventions to address this issue effectively. Notably, the study identifies autocratic leadership as a contributing factor to the rapid turnover of employees within the public sector. Conversely, employees express a greater willingness to work under a transformational leadership style. These findings underscore the importance of adopting leadership approaches that align with employee preferences and foster a positive work environment conducive to retention. The results of this study hold practical implications for public sector agencies in Jamaica and the wider Caribbean region. By recognizing the significant influence of leadership style on employee retention, organizations can develop tailored strategies to enhance retention efforts and mitigate turnover rates. Emphasizing a transformational leadership approach, coupled with improvements in the work environment and compensation, can contribute to higher levels of employee satisfaction, engagement, and ultimately, improved retention. This research paper concludes with recommendations for public sector agencies in Jamaica to implement effective leadership styles, create supportive work environments, and enhance compensation packages to improve employee retention. By addressing these key areas, the public sector can foster a motivated and committed workforce, leading to enhanced organizational performance and the provision of quality public services. Keywords: leadership, employee retention, job satisfaction, transformational leader, Jamaica